Discovering food product design by shaping sheep's cheese perception in New Zealand : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Design at Massey University, Wellington, New Zealand - Fallas, Pilar (Massey University, 2018)
The Food Industry is more interested than ever in creating value through differentiation and innovation, but often overlooks creativity as key factor in generating returns from food product experiences. This project is an exploration into how design; as a creative discipline, and food science, as a technical discipline, can more closely align and collaborate to create valuable food product experiences. To explore this nexus, I exposed myself, a food scientist, to the creative research practices of design in order to develop a new cheese product. The project is a contribution to the development of New Zealand's fledgling sheep dairy industry. I first examined New Zealanders' traditional perceptions and hidden desires in relation to sheep milk products. I then explored the different dimensions of the food object (Bassi, 2015) by developing a range of sheep's cheese products to help New Zealanders become more adventurous sheep milk product consumers.
Keywords: New products -- Design -- New Zealand; Cheese products -- New Zealand; Food -- Sensory evaluation -- Psychological aspects; Consumers -- Attitudes; Sheep milk